Ultilazation of Bakteria Pseudomonas aeruginosa and Bacillus Subtilos as Bioremediation of Metal Pb in Textile Waste - Hasibuan, Ira Aqrabi Br; Manalu, Kartika; Nasution, Rizki Amelia (Jurnal Biologi Tropis, 2024)
The Indonesian textile industry is developing to meet people's needs for clothing. 3916 industries in Indonesia exist in 2021, but the number of these industries is not balanced with liquid waste processing. One alternative way to reduce heavy metal levels in waste is bioremediation. The aim of this research is to determine how incubation time and the number of Pseudomonas aeruginosa and Bacillus subtlis bacteria influence the reduction of Pb metal levels in textile waste. Several steps include the bioremediation process, colony counting, measuring Pb metal levels, measuring temperature levels, measuring pH, and data analysis. Bioremediation results: Pseudomonas aeruginosa and Bacillus subtilis bacteria succeeded in reducing Pb metal levels in textile waste with an incubation time of 14 days. The results show that this bacterium is able to reduce Pb metal levels in textile waste with the addition of a 1:1 concentration of 56%, a 1:2 concentration of 86%, and a 2:1 concentration of 92. These results show that this bacterium is successful as a bioremediation agent in reducing Pb metal levels in waste.